(untitled) (Indian Journal of Arid Horticulture, 2025)
In order to maintain the health and vigour and to sustain the productivity, a pruning experiment was conducted on four year old "Balwant’ cultivar of aonla grown in laterite soil, planted at a spacing of 5x5m. To find out the best pruning method, six levels of pruning was performed i.e., i) Light judicious pruning, ii) Detopping of primary branches at 8 feet from ground level + removal of all secondary branches, iii) Detopping of primary branches at 8 feet from the ground level + removal of all secondary branches at 2 feet from the base of primary branches, iv) Detopping of primary branches at 8 feet from the ground level + removal of all secondary branches at I feet from the base of primary branches, v) Light judicious pruning + Detopping of plant canopy of at 8 feet from the ground level, vi) No pruning (control). Results of three consecutive years of investigation revealed that light judicious pruning of thin, overlapping, criss-crossed, dead, unproductive and looping branches gave highest fruit yield in all the three years and resulted 64.4 per cent yield increment over control when average of three years was considered. Severe pruning of primary and secondary branches caused drastic reduction of yield for two consecutive years after pruning. Judicious pruning helped to produce better sizeable and quality fruits.